A CONTRASTIVE ANALYSIS OF LIBRETTO, VOCAL TECHNIQUES, AND ORCHESTRATION IN ENGLISH AND UZBEK OPERA - Dinora Ibodullayeva Bahramjanovna; Superviser: Uralova Oysuluv Payanovna (Bright Mind Publishing, 2025)
Opera as a composite art form integrates music, drama, and staging to create a cohesive aesthetic experience. English opera, rooted in European classical traditions, evolved through the works of Henry Purcell, Benjamin Britten, and later modern innovators. Uzbek opera, on the other hand, emerged as a synthesis of Western operatic forms and the indigenous maqom tradition, particularly during the early Soviet cultural reforms . This article provides a contrastive analysis of English and Uzbek opera in terms of libretto construction, vocal techniques, and orchestration, highlighting their artistic, structural, and cultural distinctions.